Etude De L’impact De La Consanguinité Sur La Santé Des Descendants Dans La Population De Tiflet (Maroc) - Abbad Zhour; Drissi Ahmed; Abdelmajid Soulaymani; Khadmaoui Abderrazak; Oukarroum Abdallah (European Scientific Journal, ESJ, 2016)
Several studies confirm the implication of the consanguinity in health problems and some countries still preserve this marital behavior. In this study, our objective is the analysis of consanguinity’s impact on descendants’ health in the Tiflet city and its regions (Northwest of Morocco). Data was collected between June and November 2012 and it was conducted on 1000 families. The calculation of the rate of the mortality concerned 3345 alive born descendants, while the biological effects of the consanguinity study was made on 3241 descendants. The results of this study show a significant association between the consanguinity and its incidence on health, such as the morbidity, the mortality and the abortion in the descendants.